Analyzing Intersectorial Water Relationships by means of Graph Theory - Esther Velazquez Alonso (European Regional Science Association (ERSA), 2003)
The aim of this work is to demonstrate the relationships between an economy's productive sectors and the water consumption generated during productive processes. We shall study the andalusian reality, a region of southern Spain characterized by water scarcity, and we will examine whether excessive dependence on water resources which, may occur in some productive sectors, might affect not only the conservation and quality of this resource, but also have negative effects upon the solidity of the economy itself. A mixed methodology has been used, combining an Input-Output model with Graph Theory. We obtain a water Input-Output model and an intersectorial relationship matrix which is analysed by Graph Theory. Next, of a brief form, we developed to the model of water consumption and the graph most significant derivative of the water matrix. Our most important aim is to obtain the Intersectorial Water Relationships Matrix with an Input-Output model. This matrix, with order (nxn) and expressed in terms of water, represents all of the transactions which occur in the economy between the various productive sectors. Interesting conclusions can be drawn from this study, the most useful of which are the use of a mixed applied methodology and the conclusions to be drawn from the study in terms of economic policy. First, the suitability methodology's for the proposed ends has to be reiterated. This mixed methodology, combining the extended Input-Output model with the Graph Theory, has been shown to be an appropriate method for analysing the relationships established between the productive structure and the consumption of natural resources since it allows direct and indirect relationships to be established. Another relevant conclusion is that there are sectors with a high level of water consumption which are hardly ever regarded as having high consumption. This is reference to the food processing industry, construction, textiles and clothing and restaurants and hotels. Although it is true that these industries are not noteworthy direct consumers, they are large indirect consumers, their demand contributing to the scarcity of water in Andalusia and creating a situation of dependency on the resource which could even perhaps endanger the stability of the economy itself. It is important that politicians in positions of power take these sectors' high indirect consumption into account and regard not just the agricultural sectors as large water consumers. Finally, the main conclusion is that Andalusia's economic specialisation does not make a positive contribution towards water conservation and, moreover, that the regional economy's sustainability may be seriously endangered if the authorities do not take into account water limitations in their policy.
Keywords: 330